Use of pooled serum samples to determine flock-level prevalence of Anaplasma phagocytophilum antibodies in Irish sheep - John M. Gilmore; Kate O. Keefe; Christine Hurley; Mark Hennessy; Amalia Naranjo-Lucena; Seamus Fagan; John F. Mee; Timothy W.J. Keady; Shane Mc Gettrick; Anne Marie Flaherty; Rebecca Fröhlich; Maresa Sheehan; et al. (Small Ruminant Research, 2026)

DNA ‐based identification of anadromous fishes ( Alosa spp., Family Clupeidae ) in stomach contents of marine groundfish - Landon P. Falke; Stacy Rowe; Yuan Liu; Timothy F. Sheehan (Journal of Fish Biology, 2026)
Using DNA techniques for prey identification is an emerging approach for enhancing the precision and accuracy of trophic information. We evaluated the effectiveness of DNA‐based prey identification in conjunction with visual stomach content analysis of commercially important groundfish in the nearshore Gulf of Maine, with a focus on distinguishing consumed anadromous ( Alosa spp.) and closely related marine prey (Atlantic herring Clupea harengus , Atlantic menhaden Brevoortia tyrannus ). DNA barcoding of 179 consumed prey specimens provided species‐ or genus‐level identification in 122 cases (68.2%), including 104 improvements to taxonomic resolution and three conflicting results compared to visual identifications. Combining DNA‐based identifications of partially or well‐digested prey with the broader visual analysis substantially improved quantification of a diet metric, frequency occurrence, as a proxy for the relative diet contributions of anadromous and marine clupeids. Body size measurements of consumed Alosa spp. identified using DNA were consistent with year‐0 or year‐1 juvenile life stages. Possible limitations to success rates of DNA assignment included the quality of sample preservation (ethanol), reference database quality (accuracy of voucher specimen identification) and sequencing errors (miscalling of nucleotide bases). Despite this, the integration of molecular methods substantially improved the interpretability of trophic interactions involving morphologically similar prey with ecologically important differences in life history. These results highlight how the targeted application of DNA‐based prey identification can complement conventional diet analyses by improving the quantification of trophic interactions that ultimately govern ecosystem processes.

The Labrador Current cold front shaping the Atlantic salmon homing migration routes from the waters off Southern Greenland to eastern North America - Christiane Dufresne; Diane Lavoie; Martha Robertson; Julien April; Chantelle Burke; Jon Carr; Joël Chassé; Frédéric Cyr; Jason Daniels; Levi Denny; Shelley Denny; Guoqi Han; et al. (Progress in Oceanography, 2025)

Trophic ecology of groundfishes in nearshore areas of the Gulf of Maine - Landon P. Falke; Brian E. Smith; Stacy Rowe; Rebecca J. Peters; Timothy F. Sheehan (Journal of Fish Biology, 2025)
Ecosystem management requires an integrated understanding of ecological interactions. In the Gulf of Maine (GoM), trophic information pertaining to commercially important groundfishes and nearshore prey communities is lacking. We characterized nearshore communities and groundfish diets using data collected from nearshore surveys (864 bottom trawls and 3638 stomach samples of six groundfish species) conducted biannually (spring and fall) in Midcoast Maine and Penobscot Bay from 2012 to 2022. Groundfish diets were dominated by some of the most available nearshore prey (gadiform and clupeiform fishes and pandalid and crangonid shrimps). Shifts in relative prey availability over environmental gradients (e.g., depth and position along the coast), across seasons, and over years corresponded with parallel patterns in prey contributions to groundfish diets in specific predator–prey interactions. Negative trends in the relative availability and diet occurrence of signature GoM prey taxa (Northern shrimp Pandalus borealis , Atlantic herring Clupea harengus , and euphausiids) indicate that broader ecosystem changes, such as steady rises in water temperature and shifts in species distributions, are impacting nearshore trophic dynamics in the GoM. These observations provide timely information on mechanisms that underlie groundfish productivity and warrant inclusion of nearshore trophic dynamics in relevant ecosystem models.

Examining fish scale biomineral from Atlantic salmon populations - Elizabeth Tray; Deirdre Brophy; Elvira de Eyto; Niall Ó'Maoileidigh; Timothy Sheehan; Ian Bradbury; Quentin G. Crowley (Journal of Fish Biology, 2024)
Fish scale microchemistry can be used to make life‐history inferences, although ecological studies examining scale composition are relatively rare. Salmon scales have an external layer of calcium phosphate hydroxyl apatite (HAP). The structure, hardness, and calcium content of this layer have been shown to vary within and between species. This variation may lead to misinterpretation of trace element profiles. This study uses backscatter scanning electron microscopy with electron dispersive spectrometry to compare scales from salmon populations and to present a more detailed analysis of scale HAP than was previously available. Our findings extend the range of salmon populations for which HAP Ca is available and confirm previous findings that the HAP Ca is relatively invariable within this species.

A novel climate and health decision support platform: Approach, outputs, and policy considerations - Jeremy J. Hess; Timothy J. Sheehan; Alyssa Miller; Rad Cunningham; Nicole A. Errett; Tania Busch Isaksen; Jason Vogel; Kristie L. Ebi (Environmental Research, 2023)

What Have We Lost? Modeling Dam Impacts on American Shad Populations Through Their Native Range - Joseph Zydlewski; Daniel S. Stich; Samuel Roy; Michael Bailey; Timothy Sheehan; Kenneth Sprankle (Frontiers in Marine Science, 2021)
American shad ( Alosa sapidissima ) are native to the east coast of North America from the St. Johns River, Florida, to the St. Lawrence River region in Canada. Since the 1800s, dams have reduced access to spawning habitat. To assess the impact of dams, we estimated the historically accessed spawning habitat in coastal rivers (485,618 river segments with 21,113 current dams) based on (i) width, (ii) distance from seawater, and (iii) slope (to exclude natural barriers to migration) combined with local knowledge. Estimated habitat available prior to dam construction (2,752 km 2 ) was 41% greater than current fully accessible habitat (1,639 km 2 ). River-specific population models were developed using habitat estimates and latitudinally appropriate life history parameters (e.g., size at age, maturity, iteroparity). Estimated coast-wide annual production potential was 69.1 million spawners compared with a dammed scenario (41.8 million spawners). Even with optimistic fish passage performance assumed for all dams (even if passage is completely absent), the dam-imposed deficit was alleviated by fewer than 3 million spawners. We estimate that in rivers modeled without dams, 98,000 metric tons of marine sourced biomass and nutrients were annually delivered, 60% of which was retained through carcasses, gametes and metabolic waste. Damming is estimated to have reduced this by more than one third. Based on our results, dams represent a significant and acute constraint to the population and, with other human impacts, reduce the fishery potential and ecological services attributed to the species.

Date of marine annulus formation in A tlantic salmon ( Salmo salar ) and implications for retrospective growth analyses using scales - Lindsay G. Carlson; Timothy F. Sheehan; Michael D. Tillotson; Katherine E. Mills (Journal of Fish Biology, 2021)
Fish scales have increasingly been used to quantify annual and seasonal growth trends and in efforts to relate growth to environmental conditions. Understanding the timing of formation of an annulus (a group of narrowly spaced circuli) is critical when assessing the influence of marine ecosystem conditions on seasonal growth patterns of Atlantic salmon, yet the literature does not provide consistent answers regarding the timing or drivers of marine annulus formation. This study demonstrates a novel method for estimating stock‐specific annulus formation timing based on marked individuals with known emigration and return/recovery dates. An equation was applied to estimate the date of annulus completion for Atlantic salmon ( Salmo salar ) using known dates, number of circuli after the most recent annulus and marine circulus deposition rate. Five marine circulus deposition rate scenarios were tested, some of which accounted for individual, seasonal and age‐related variability and others which use previously published marine circulus deposition rates. Based on these results, an argument is presented to reconsider the practice of assigning annulus formation dates to winter solstice in favour of dates estimated by a scenario that accounts for individual, seasonal and age‐related variation in circulus deposition. This scenario suggests that annulus formation occurs between mid‐February and late March. In this case, the annulus would be formed during the coldest part of the year in the primary overwintering area for North American Atlantic salmon.

Spatial synchrony in the response of a long range migratory species ( Salmo salar ) to climate change in the North Atlantic Ocean - Maxime Olmos; Mark R. Payne; Marie Nevoux; Etienne Prévost; Gérald Chaput; Hubert Du Pontavice; Jérôme Guitton; Timothy Sheehan; Katherine Mills; Etienne Rivot (Global Change Biology, 2020)
A major challenge in understanding the response of populations to climate change is to separate the effects of local drivers acting independently on specific populations, from the effects of global drivers that impact multiple populations simultaneously and thereby synchronize their dynamics. We investigated the environmental drivers and the demographic mechanisms of the widespread decline in marine survival rates of Atlantic salmon ( Salmo salar ) over the last four decades. We developed a hierarchical Bayesian life cycle model to quantify the spatial synchrony in the marine survival of 13 large groups of populations (called stock units, SU) from two continental stock groups (CSG) in North America (NA) and Southern Europe (SE) over the period 1971–2014. We found strong coherence in the temporal variation in postsmolt marine survival among the 13 SU of NA and SE. A common North Atlantic trend explains 37% of the temporal variability of the survivals for the 13 SU and declines by a factor of 1.8 over the 1971–2014 time series. Synchrony in survival trends is stronger between SU within each CSG. The common trends at the scale of NA and SE capture 60% and 42% of the total variance of temporal variations, respectively. Temporal variations of the postsmolt survival are best explained by the temporal variations of sea surface temperature (SST, negative correlation) and net primary production indices (PP, positive correlation) encountered by salmon in common domains during their marine migration. Specifically, in the Labrador Sea/Grand Banks for populations from NA, 26% and 24% of variance is captured by SST and PP, respectively and in the Norwegian Sea for populations from SE, 21% and 12% of variance is captured by SST and PP, respectively. The findings support the hypothesis of a response of salmon populations to large climate‐induced changes in the North Atlantic simultaneously impacting populations from distant continental habitats.

Medication reconciliation: time to save? A cross-sectional study from one acute hospital - Elaine K. Walsh; Ann Kirby; Patricia M. Kearney; Colin P. Bradley; Aoife Fleming; Kieran A. O’Connor; Ciaran Halleran; Timothy Cronin; Elaine Calnan; Patricia Sheehan; Laura Galvin; Derina Byrne; et al. (European Journal of Clinical Pharmacology, 2019)

Presence and genetic variability of Piscine orthoreovirus genotype 1 (PRV‐1) in wild salmonids in Northern Europe and North Atlantic Ocean - Niccoló Vendramin; Argelia Cuenca; Juliane Sørensen; Anna L. F. Alencar; Debes H. Christiansen; Jan A. Jacobsen; Charlotte Axen; François Lieffrig; Neil M. Ruane; Patrick Martin; Timothy Sheehan; Tine M. Iburg; et al. (Journal of Fish Diseases, 2019)
Piscine orthoreovirus genotype 1 (PRV‐1) is widespread in farmed Atlantic salmon ( Salmo salar L.) populations in northern Europe, Canada and Chile. PRV‐1 occurs in wild fish in Norway and Canada; however, little information of its geographical distribution in wild populations is currently available, and the effect of PRV‐1 infection in wild populations is currently unknown. In this study, we present the findings of a survey conducted on 1,130 wild salmonids sampled in Denmark, Sweden, Ireland, Faroe Islands, France, Belgium and Greenland between 2008 and 2017. PRV‐1 is reported for the first time in wild salmonids in Denmark, Sweden, Faroe Island and Ireland. The annual PRV‐1 prevalence ranged from 0% in France, Belgium and Greenland to 43% in Faroe Islands. In total, 66 samples tested positive for PRV‐1, including Atlantic salmon broodfish returning to spawn and Atlantic salmon collected at the feeding ground north of Faroe Islands. The phylogenetic analysis of S1 sequences of the PRV‐1 isolates obtained in this survey did not show systematic geographical distribution. This study sheds light on the spread and genetic diversity of the virus identified in populations of free‐living fish and provides rationale for screening wild broodfish used in restocking programmes.

Demographic and genetic description of Greenland's only indigenous Atlantic salmon Salmo salar population - Jo V. Arnekleiv; Jan G. Davidsen; Timothy F. Sheehan; Sarah J. Lehnert; Ian R. Bradbury; Lars Rønning; Aslak D. Sjursen; Gaute Kjærstad; Barbara A. Lubinski; Kjell J. Nilssen (Journal of Fish Biology, 2019)
A survey of the Kapisillit River system was conducted in 2005 and 2012 to study the only indigenous Atlantic salmon Salmo salar population in Greenland. Little is known about its characteristics or its relationship with other S. salar populations across the species range. Juvenile S. salar were captured in all stations surveyed within the lower river with the highest densities lower in the river and decreasing densities with increasing distance from the river mouth. Captured juveniles ranged from 0+ to 7+ years old and the predominant smolt age was between 4 and 6 years. Median length of 0+ and 1+ juveniles in August–September was 38.8 and 70.4 mm, respectively. The proportion of mature male parr increased from 4% for 1+ year old fish to 95% for fish greater than 2 years old. Genetic analysis using 96 single nucleotide polymorphisms (SNP) revealed a high degree of genetic similarity between collections, extremely low genetic diversity and low estimates of effective population size ( N e = 28.7; 95% CI = 19.7–42.4). Genetic comparison to range‐wide S. salar populations demonstrated that the Kapisillit River S. salar is an outgroup of the eastern Atlantic stock complex, which is consistent with the hypothesised colonisation from the east. River morphology and the absence of glacier runoff are hypothesised to be the main reasons for the relatively high river temperatures supporting this self‐sustaining population of S. salar . Given its uniqueness and persistence, this population represents an important part of range‐wide biodiversity of S. salar .

Assessing the diet of North American Atlantic salmon ( Salmo salar L.) off the West Greenland coast using gut content and stable isotope analyses - Heather J. Dixon; J. Brian Dempson; Timothy F. Sheehan; Mark D. Renkawitz; Michael Power (Fisheries Oceanography, 2017)
Investigations on the marine feeding of Atlantic salmon ( Salmo salar L.) in the Northwest Atlantic are limited compared with the Northeast Atlantic. Climate‐induced changes to food webs in Atlantic salmon feeding areas have been noted, alongside increased mortality despite a cessation of most marine fisheries. As forage efficiency may be hampering survival, it was important to address this knowledge gap. Atlantic salmon were sampled at three sites on the West Greenland coast (Sisimiut, Nuuk and Qaqortoq) between 2009 and 2011. Gut content and stable isotope analyses were combined to assess spatial and temporal differences in feeding. Capelin ( Mallotus villosus ) dominated the diet at Nuuk and Qaqortoq, whereas boreoatlantic armhook squid ( Gonatus fabricii ) was the dominant prey at Sisimiut. Hyperiid amphipods ( Themisto spp.) and sand lance ( Ammodytes spp.) were also important. Significant differences were found among sites for both gut contents and stable isotope analyses, with fewer differences evident temporally. Dietary differences were also evident across larger scales, with little overlap demonstrated with Northeast Atlantic diets and the emergence of boreoatlantic armhook squid as an important prey item over time. Atlantic salmon diets are frequently anchored on one or two prey items, on which they appear to specialize, but they will diversify to consume other available pelagic prey. Thus, Atlantic salmon are an opportunistic, generalist predator within the pelagic food web. The variability evident in diet suggests that the limited data available are insufficient to appropriately understand potential vulnerabilities that the species may have to ecosystem changes, and suggest further research is needed.

Projected carbon stocks in the conterminous USA with land use and variable fire regimes - Dominique Bachelet; Ken Ferschweiler; Timothy J. Sheehan; Benjamin M. Sleeter; Zhiliang Zhu (Global Change Biology, 2015)
The dynamic global vegetation model ( DGVM ) MC 2 was run over the conterminous USA at 30 arc sec (~800 m) to simulate the impacts of nine climate futures generated by 3 GCM s ( CSIRO , MIROC and CGCM 3) using 3 emission scenarios (A2, A1B and B1) in the context of the LandCarbon national carbon sequestration assessment. It first simulated potential vegetation dynamics from coast to coast assuming no human impacts and naturally occurring wildfires. A moderate effect of increased atmospheric CO 2 on water use efficiency and growth enhanced carbon sequestration but did not greatly influence woody encroachment. The wildfires maintained prairie‐forest ecotones in the Great Plains. With simulated fire suppression, the number and impacts of wildfires was reduced as only catastrophic fires were allowed to escape. This greatly increased the expansion of forests and woodlands across the western USA and some of the ecotones disappeared. However, when fires did occur, their impacts (both extent and biomass consumed) were very large. We also evaluated the relative influence of human land use including forest and crop harvest by running the DGVM with land use (and fire suppression) and simple land management rules. From 2041 through 2060, carbon stocks (live biomass, soil and dead biomass) of US terrestrial ecosystems varied between 155 and 162 Pg C across the three emission scenarios when potential natural vegetation was simulated. With land use, periodic harvest of croplands and timberlands as well as the prevention of woody expansion across the West reduced carbon stocks to a range of 122–126 Pg C, while effective fire suppression reduced fire emissions by about 50%. Despite the simplicity of our approach, the differences between the size of the carbon stocks confirm other reports of the importance of land use on the carbon cycle over climate change.

Retrospective analysis of A tlantic salmon ( Salmo salar ) marine growth and condition in the northwest A tlantic based on tag‐recovery data - Alicia S. Miller; Timothy J. Miller; Katherine E. Mills; Timothy F. Sheehan (Fisheries Oceanography, 2014)
The life history of N orth A merican A tlantic salmon ( S almo salar ) is characterized by extensive round‐trip migrations between freshwater rearing habitats and marine feeding grounds off the coasts of C anada and G reenland. Growth is rapid during the marine migration, and growth rate and condition factor may be indicators of salmon health during this period. Growth data were evaluated from a tag‐recovery program conducted from 1969 to 1991 using hatchery‐reared A tlantic salmon smolts released in the P enobscot R iver, M aine, U.S.A. Information from recaptures of 3167 salmon that were at large in the marine environment for 1 month to 3 yr was analyzed. Length–weight measurements coupled with time‐at‐large data were used to estimate von Bertalanffy and allometric growth parameters specific to the marine phase. Variations in growth and condition factor in relation to smolt age, release date, and temperature conditions in the northwest Atlantic were also examined. The von Bertalanffy k parameter declined with ordinal release date, indicating faster growth rates during the first year of smolts released earlier in the spring. The 2‐yr‐old smolts had a larger k than 1‐yr‐old smolts, although 1‐yr‐old smolts grew to a larger asymptotic size. Sea surface temperature had variable effects on growth parameters and condition factor, with temperature at the beginning of the migration and in overwintering habitat during the first year at sea having the greatest influence on length–weight relationships. Determining the mechanisms that influence growth of individuals during the marine phase will help elucidate the factors responsible for historic growth trends, establishing a baseline for current research.

Climate and ecosystem linkages explain widespread declines in North American Atlantic salmon populations - Katherine E. Mills; Andrew J. Pershing; Timothy F. Sheehan; David Mountain (Global Change Biology, 2013)
North American Atlantic salmon ( Salmo salar ) populations experienced substantial declines in the early 1990s, and many populations have persisted at low abundances in recent years. Abundance and productivity declined in a coherent manner across major regions of North America, and this coherence points toward a potential shift in marine survivorship, rather than local, river‐specific factors. The major declines in Atlantic salmon populations occurred against a backdrop of physical and biological shifts in Northwest Atlantic ecosystems. Analyses of changes in climate, physical, and lower trophic level biological factors provide substantial evidence that climate conditions directly and indirectly influence the abundance and productivity of North American Atlantic salmon populations. A major decline in salmon abundance after 1990 was preceded by a series of changes across multiple levels of the ecosystem, and a subsequent population change in 1997, primarily related to salmon productivity, followed an unusually low NAO event. Pairwise correlations further demonstrate that climate and physical conditions are associated with changes in plankton communities and prey availability, which are ultimately linked to Atlantic salmon populations. Results suggest that poor trophic conditions, likely due to climate‐driven environmental factors, and warmer ocean temperatures throughout their marine habitat area are constraining the productivity and recovery of North American Atlantic salmon populations.

Microbially mediated sulphide production in a thermal, acidic algal mat community in Yellowstone National Park - Michael J. Ferris; Timothy S. Magnuson; Jennifer A. Fagg; Roland Thar; Michael Kühl; Kathy B. Sheehan; Joan M. Henson (Environmental Microbiology, 2003)
Summary Our objective in this study was to characterize prokaryotic sulphide production within the oxygenic, predominantly eukaryotic algal mat in an acidic stream, Nymph Creek, in Yellowstone National Park (YNP). We used microsensors to examine fluctuations in H 2 S and O 2 concentrations over time through the vertical aspect of the ∼3 mm mat in a 46–48°C region of the creek. We also used analyses of PCR‐amplified 16S rRNA gene sequences obtained from denaturing gradient gels, and PCR‐amplified sequences of a functional gene associated with microbial sulphate respiration ( dsrA ) to characterize the bacterial community in the same region of the mat. During midday, photosynthesis rates were high within the first 500 µm interval of the mat and high oxygen concentrations (600% air saturation) penetrated deeply (>1800 µm) into the mat. During early evening and night, oxygen concentrations within the first 1100 µm of the mat decreased over time from 60% air saturation (a.s) to 12% a.s. A precipitous decline in oxygen concentration occurred at a depth of 1100 µm in all night measurements and anoxic conditions were present below 1200 µm. Within this anoxic region, sulphide concentrations increased from nearly 0 µM at 1200 µm depth to 100 µM at 2400 µm depth. Enrichment cultures inoculated with Nymph Creek mat organisms also produced H 2 S. Sequence analyses of 16S rRNA and dsrA genes indicated the presence of at least five bacterial genera including species involved in dissimilative sulphate or sulphur reduction.